CO bond formation in a microfluidic reactor: high yield SNAr substitution of heteroaryl chlorides. Issue 19 (11th May 2016) - Alam, Mohammad Parvez; Jagodzinska, Barbara; Campagna, Jesus; Spilman, Patricia; John, Varghese
Graphical abstract: Highlights: Green chemistry, efficient procedure for CO bond formation under mild conditions. Continuous flow, rapid, CO bond formation in a microfluidic reactor. High yield CO bond formation in electron deficient pyrimidines and pyridines. General utility to make CO bond containing intermediates of industrial importance. Abstract: This study describes our development of a novel and efficient procedure for CO bond formation under mild conditions, for coupling heteroaryl chlorides with phenols or primary aliphatic alcohols. We utilized a continuous-flow microfluidic reactor for CO bond formation in electron-deficient pyrimidines and pyridines in a much more facile manner with a cleaner reaction profile, high yield, quick scalability, and without the need for the transition metal catalyst. This approach can be of general utility to make CO bond containing intermediates of industrial importance in a continuous and safe manner.